Nanopore DNA Sequencing and Genome Assembly on the International Space Station. Issue 1 (December 2017) - Castro-Wallace, Sarah; Chiu, Charles; John, Kristen; Stahl, Sarah; Rubins, Kathleen; McIntyre, Alexa; Dworkin, Jason; Lupisella, Mark; Smith, David; Botkin, Douglas; Stephenson, Timothy; Juul, Sissel; et al.
Abstract We evaluated the performance of the MinION DNA sequencer in-flight on the International Space Station (ISS), and benchmarked its performance off-Earth against the MinION, Illumina MiSeq, and PacBio RS II sequencing platforms in terrestrial laboratories. Samples contained equimolar mixtures of genomic DNA from lambda bacteriophage, Escherichia coli (strain K12, MG1655) andMus musculus (female BALB/c mouse). Nine sequencing runs were performed aboard the ISS over a 6-month period, yielding a total of 276, 882 reads with no apparent decrease in performance over time. From sequence data collected aboard the ISS, we constructed directed assemblies of the 4.6 MbE. coli genome, 48.5 kb lambda genome, and a representativeM. musculus sequence (the 16.3 kb mitochondrial genome), at 100%, 100%, and 96.7% consensus pairwise identity, respectively;de novo assembly of theE. coli genome from raw reads yielded a single contig comprising 99.9% of the genome at 98.6% consensus pairwise identity. Simulated real-time analyses of in-flight sequence data using an automated bioinformatic pipeline and laptop-based genomic assembly demonstrated the feasibility of sequencing analysis and microbial identification aboard the ISS. These findings illustrate the potential for sequencing applications including disease diagnosis, environmental monitoring, and elucidating the molecular basis for how organisms respond to spaceflight.